The relationship between Antarctic sea-ice extent change and the main modes of sea-ice variability in austral winter - Lejiang Yu; Cuijuan Sui; Haixia Dai (Polar Research, 2024)
Accompanying global warming, Antarctic sea-ice extent shows a somewhat increasing trend from 1979 to 2014, followed by an abrupt decrease after 2016. Our previous study examined the change of Antarctic sea-ice extent in austral summer, autumn and spring. In this study, we turn our attention to the austral winter, relating the main modes of sea-ice variability to sea-ice extent in the Pacific, Atlantic and Indian sectors of the Southern Ocean. We find that the modes with the strongest correlation with the sea-ice extent are the third, first and first modes in the Pacific, Atlantic and Indian sectors, respectively. Atmospheric circulation anomalies of zonal wavenumber three over the Southern Ocean, related to planetary wave trains induced by the SST anomalies over the south-western Pacific and the southern Indian oceans, can explain sea-ice concentration anomalies of the third mode in the Pacific sector through thermodynamic and dynamic processes. Sea-ice anomalies of the first modes in the Atlantic and Indian sectors result from atmospheric circulation anomalies of a positive and negative phases of the Southern Annular Mode, respectively. The anomalous Southern Annular Mode is also associated with wave trains over the Southern Ocean excited by SST anomalies over the southern Indian Ocean and the south-western Pacific Ocean. The relationship between SST anomalies and Antarctic sea-ice anomalies can provide a reference for the prediction of Antarctic sea-ice anomalies in austral winter on interannual and decadal timescales.